2019
DOI: 10.3390/pharmaceutics11090472
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Capsid Protein-Derived Nanoparticles and Polymers as Versatile Platforms for Antigen Presentation and Vaccine Development

Abstract: Major viral structural proteins interact homotypically and/or heterotypically, self-assembling into polyvalent viral capsids that usually elicit strong host immune responses. By taking advantage of such intrinsic features of norovirus capsids, two subviral nanoparticles, 60-valent S60 and 24-valent P24 nanoparticles, as well as various polymers, have been generated through bioengineering norovirus capsid shell (S) and protruding (P) domains, respectively. These nanoparticles and polymers are easily produced, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 82 publications
(137 reference statements)
2
20
0
Order By: Relevance
“…The results showed that the PVNPs bound only 2,3-linked, but not 2,6- or 2,8-linked sialoglycans (Fig. 6(b)), consistent with the known receptor binding nature of their parental H7N9 avian IVs [35,37,38]. Accordingly, the S 60 -HA1 PVNPs agglutinated human RBCs at a high hemagglutination titer of 122 ng/mL (Fig.…”
Section: Ha1ssupporting
confidence: 73%
“…The results showed that the PVNPs bound only 2,3-linked, but not 2,6- or 2,8-linked sialoglycans (Fig. 6(b)), consistent with the known receptor binding nature of their parental H7N9 avian IVs [35,37,38]. Accordingly, the S 60 -HA1 PVNPs agglutinated human RBCs at a high hemagglutination titer of 122 ng/mL (Fig.…”
Section: Ha1ssupporting
confidence: 73%
“…In terms of applications, it may be possible to engineer this virus into a vaccine candidate that can present some of the conserved antigenic domains but have little to no risk of causing the activity or pathogenesis seen in the VP34/27/25 capsid. Similar systems have precedent in other viruses, such as norovirus capsid-derived nanoparticles [ 58 ].…”
Section: Engineering and Practical Applications Of Astv Structural Proteins And Vlpsmentioning
confidence: 99%
“…To develop a nonreplicating vaccine for parenteral use, a P 24 -VP8* nanoparticle has been generated as a rotavirus vaccine candidate [ 14 , 15 , 16 ]. Each nanoparticle is composed of a 24 valent P 24 nanoparticle core [ 17 , 18 ] made by 24 norovirus protruding (P) domains and 24 rotavirus VP8* antigens that are displayed on the surface of the nanoparticle.…”
Section: Introductionmentioning
confidence: 99%